Inclusiveness in Gurukul Education System - Adhikari, Toya Nath (Gyanjyoti, 2023)
Education is as a jewel for human being. It enhances human dignity and prestige in the society. An educated person is also appreciated everywhere. Likewise, happiness is not less than the happiness that mother gives to man through education. It makes people strong. Therefore, education or knowledge is a precious asset of any person. Schooling is very significant to communicate knowledge for the generations to come. Schooling offers skills for people to receive their livelihood so that the lifestyle of people will be developed to make independence. Nowadays, there are worldwide practices on education around the world. Similarly, the education system needs to be relevant to the demand of the diverse culture, languages, ethnicity and tradition of a country. One of the practices in the field of education is the Gurukul education system. This is because all languages, cultures and civilizations of ancient times are in world heritage. According to the eastern philosophy in educational practices, that was mostly well recognized in the eastern part of the world such as India and Nepal. The Gurukul education system is the oldest and most former system of education in the present world. So, the purpose of this research study is to present the inclusiveness in Gurukul Education System.